Karuna Dipa 1981-1994: History and Development of Buddhist Schools in Palu City - M. Syahid; Lukman Nadjamudin; Haliadi; Windayanti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The research on the history of Buddhist schools in Palu City began from the author's interest in the unique educational system of Central Sulawesi. It traces the founding of Karuna Dipa schools, starting with the inception of the foundation idea, its naming background, and the initial formation process, culminating in the establishment of Karuna Dipa High School in 1994. The study aims to describe the establishment background of the Karuna Dipa Foundation, the development of its schools, and the progress of those schools under the foundation's umbrella. It employs historical methodology, including source collection, verification, analysis, and historical writing. Key findings include: (1) The foundation of the Karuna Dipa Foundation was initiated with its naming by Bhikkhu Sri Pannavaro Mahatthera on June 29, 1981, and formalized in its charter on October 8, 1982. (2) The foundation was established by the Chinese-Indonesian community to create a Buddhist school with superior environment and quality in Palu City. (3) Karuna Dipa Kindergarten opened on July 13, 1983, Karuna Dipa Elementary School admitted new students in the academic year 1985/1986, Karuna Dipa Junior High School accepted new students on July 17-16, 1991, and Karuna Dipa High School was founded in 1994 and accredited as a private institution. These schools, focusing on Buddhist teachings, were established by ethnic Chinese individuals in Palu City to provide better educational opportunities.